Knowing One’s Place: Parental Educational Background Influences Social Identification with Academia, Test Anxiety, and Satisfaction with Studying at University - Janke, Stefan; Rudert, Selma C.; Marksteiner, Tamara; Dickhäuser, Oliver (Frontiers in Psychology, 2017)
First-generation students (i.e., students whose parents did not attend university) often experience difficulties fitting in with the social environment at universities. This experience of personal misfit is supposedly associated with an impaired social identification with their aspired in-group of academics compared to continuing-generation students (i.e., students with at least one parent with an academic degree. In this article, we investigate how the postulated differences in social identification with the group of academics affect first-generation students’ satisfaction with studying and test anxiety over time. We assume that first-generation students’ impaired social identification with the group of academics leads to decreased satisfaction with studying and aggravated test anxiety over the course of the first academic year. In a longitudinal study covering students’ first year at a German university, we found that continuing-generation students consistently identified more strongly with their new in-group of academics than first-generation students. The influence of social identification on test anxiety and satisfaction with studying differed between groups. For continuing-generation students, social identification with the group of academics buffered test anxiety and helped them maintain satisfaction with studying over time. We could not find these direct effects within the group of first-generation students. Instead, first-generation students were more sensitive to effects of test anxiety on satisfaction with studying and vice versa over time. The results suggest that first-generation students might be more sensitive to the anticipation of academic failure. Furthermore, continuing-generation students’ social identification with the group of academics might have buffered them against the impact of negative experiences during the entry phase at university. Taken together, our findings underscore that deficit-driven approaches focusing solely on first-generation status may not be sufficient to fully understand the importance of parental educational background for students’ well-being. More specifically, continuing-generation students might reap benefits from their parental educational background. These benefits widen the social gap in academia in addition to the disadvantages of students with first-generation status. In sum, understanding the benefits of continuing-generation status has important implications for interventions aiming to reduce social class gaps in academia.